The impact of "faster aspart" on blood glucose control in children and adolescents with type 1 diabetes treated using a sensor-augmented insulin pump - Jesús González de Buitrago Amigo; Ana González García; Paula Díaz Fernández; Mercedes Fernández Llamas; María Luz Tejado Bravo; Jorge M. de Nicolás Jiménez; Marta Ferrer Lozano (Elsevier, 2021)
Background and aims: Post-prandial glucose control is essential to achieve metabolic goals in patients with type 1 diabetes mellitus (T1DM). The new "faster aspart" insulin has a pharmacological profile noted for its faster absorption and onset of action, and increased early availability, resulting in improved blood glucose control after meals. The main objective of the study was to analyse the efficacy of "faster aspart" vs. "insulin aspart" in children and adolescents with DM1 on sensor-augmented pump treatment. Patients and methods: Multicentre, longitudinal and prospective analytical trial evaluating the use of faster aspart insulin for three months in children with T1DM with MiniMed640G® sensor-augmented pumps previously treated with aspart insulin. At the beginning and end of the study the following variables were analysed for subsequent comparison: mean sensor glucose, percentage of time in range, hypoglycaemia and hyperglycaemia, area under the curve (AUC) <70 and >180 mg/dL, mean sensor glucose pre- and postprandial in main meals, daily insulin requirements, basal/bolus percentage, and HbA1c. Acute complications, adverse events and satisfaction survey were assessed. Results: The study included 32 patients with a mean of 13.49 ± 2.42 years of age and with T1DM of 7.0 ± 3.67 years of onset. The use of faster aspart was associated with lower time in hyperglycaemia >180 mg/dL (25.8 ± 11.3 vs. 22.4 ± 9.5; p = .011) and >250 mg/dL (5.2±4.9 vs. 4.0 ± 3.6; p = .04), lower AUC >180 mg/dL (10.8 ± 6.5 vs. 9.3 ± 6.1; p = .03), and increased time in range (71.4 ± 10.0 vs. 74.3 ± 9.2; p = .03). No significant changes in hypoglycaemia, HbA1c, insulin requirements, and basal/bolus percentages were detected. Faster aspart was safe and well-evaluated by patients and caregivers. Conclusions: Faster aspart achieves better glycaemic control by increasing glucose time in range in children and adolescents with T1DM on treatment with sensor-augmented pumps. Resumen: Introducción y objetivos: El control glucémico postprandial es fundamental para conseguir los objetivos metabólicos en pacientes con diabetes mellitus tipo 1 (DM1). La nueva insulina faster aspart presenta un perfil farmacológico caracterizado por una absorción e inicio de acción más rápidos, mayor disponibilidad precoz y menor incremento de la glucosa postprandial. El objetivo principal del estudio fue analizar su eficacia en pacientes con DM1 tratados con un sistema integrado. Pacientes y métodos: Estudio analítico, longitudinal, prospectivo y multicéntrico, evaluando el empleo de faster aspart durante tres meses en pacientes en edad pediátrica con DM1 con sistema integrado MiniMed640G® tratados previamente con insulina aspart. Al inicio y final del estudio se analizaron para posterior comparación: glucosa media, porcentajes de tiempo en objetivo, tiempo en hipoglucemia e hiperglucemia, área bajo la curva (AUC) <70 y >180 mg/dL, glucosa media pre y postprandial en comidas principales, necesidades diarias de insulina, porcentaje basal/bolo y HbA1c. Se registraron complicaciones agudas y eventos adversos, y se evaluó grado de satisfacción mediante encuesta. Resultados: Se incluyeron 32 pacientes de 13,49 ± 2,42 años de edad con DM1 de 7,0 ± 3,67 años de evolución. Faster aspart se asoció a menor porcentaje de tiempo en hiperglucemia >180 mg/dL (25,8 ± 11,3 vs. 22,4 ± 9,5; p = 0,011) y >250 mg/dL (5,2 ± 4,9 vs. 4,0 ± 3,6; p = 0,04) y AUC >180 mg/dL (10,8 ± 6,5 vs. 9,3 ± 6,1; p = 0,03), incrementándose el tiempo en objetivo (71,4 ± 10,0 vs. 74,3 ± 9,2; p = 0,03) sin aumentar hipoglucemias. Las necesidades de insulina, porcentajes basal/bolo y HbA1c no se modifican significativamente. Faster aspart fue bien tolerada y valorada por los participantes. Conclusiones: Faster aspart consigue un mejor control glucémico, aumentando el tiempo de glucosa en objetivo en niños y adolescentes con DM1 en tratamiento con un sistema integrado.